What a pickle - Han, Lilly Li Li (2018)
Pickle is to preserve food in vinegar or salty water and, it can also mean being in a difficult situation. What a pickle is a project on food waste and what a pickle it is. The project aims to create a space for consumers to wonder about food and discover their own meaning and stories to not waste the food they love; in hopes of discovering nostalgic memories and insights to why they eat what they eat, and preserve what they have found out and remember to make better choices to reduce food waste.